All these bodies - Blake, Kendare (Quill Tree Books, 2021)
In the late 1950s in the Midwest, a serial killer has been draining their victims of blood, leaving them otherwise undisturbed in their cars and homes. When a fifteen-year-old girl is found covered in blood amidst the latest corpses, she confides only in the sheriff's son but her story is unbelievable at best.